Ideas Old and New: Bharatiyakaran/Indianisation of Social Work. Issue 3 (September 2019) - Kumar, Ajit
Abstract: This article discusses the current development of Bharatiyakaran /Indianisation of social work education and practice in India. Drawing on relevant information from Bharatiyakaran workshops and conferences, it analyses mission and motives, and prospects and perils of Bharatiyakaran . The Indic-religions and emic approach are crafting a unique form of the Indian religio-cultural nationalism. The Bharatiyakaran advocates assert that their initiatives of de-colonisation, Indianisation and indigenisation would challenge the Eurocentric domination of the Indian social work. While indigenisation of social work in India is overdue, the current Bharatiyakaran trend raises more contradictions and questions.